Fabrication and Modeling of Integrated Micro-Thermoelectric Cooler by Template-Assisted Electrochemical Deposition. (6th January 2017) - Garcia, Javier; Ramos, David Alberto Lara; Mohn, Melanie; Schlörb, Heike; Rodriguez, Nicolas Perez; Akinsinde, Lewis; Nielsch, Kornelius; Schierning, Gabi; Reith, Heiko
Abstract : In this work, we report on the structured electrochemical deposition of smooth and compact 12 μm thick films of Bi2 (Tex Se1-x )3 and (Bix Sb1-x )2 Te3 thermoelectric compounds. Furthermore, these materials are used as p and n-type semiconductors to fabricate a highly compact micro-thermoelectric cooler with cross-sections of the single legs and gaps between the legs in the order of 20 × 100 μm² and 8 μm, respectively. The whole process has been developed with the aim of integrating the cooling device directly on a photoelectronic integrated circuit (PIC). The complex structure of the PICs including different structure heights makes the implementation of mechanical polishing or bonding processes difficult. The electrodeposition of the materials in such small structures comes together with an edge effect that is translated in an extremely fast and dendritic growth. Direct ultrasonication of the electrolyte during the depositions has shown best results completely overcoming the edge effect, thus allowing to produce well defined structures with high spatial resolution. Moreover, this study is complemented by the analysis of the cooling performance by finite element simulations using experimental thermoelectric properties measured on continuous films.